Binuclear ketodiiminate magnesium complexes for the ROP of cyclic l-Lactide and ε-Caprolactone. (1st August 2022) - Glöckler, Eduard; Ghosh, Swarup; Wölper, Christoph; Coban, Deniz; Gröschel, André H.; Schulz, Stephan
Graphical abstract: Abstract: In contrast to well-established linear and branched polyesters, which find widespread biomedical and materials applications, cyclic polyesters have been less explored. We report on ketodiiminate magnesium complexes L 1 2 Mg3 Cp + MgCp3 - (1 ), L 1 (MgCp*)2 (2 ) and L 2 (MgCp)2 (3 ) (L 1 = (Me2 NC2 H4 NC(Me)CH)2 CO, L 2 = (Me2 NC3 H6 NC(Me)CH)2 CO), which were spectroscopically characterized ( 1 H, 13 C NMR, IR) as well as by elemental analysis and single crystal X-ray diffraction (sc-XRD). Complexes 1 –3 were used in the ring-opening polymerization (ROP) of l -lactide ( L -LA) and ε -caprolactone ( ε -CL) under mild reaction conditions. Catalyst 2 showed excellent reactivity and selectivity for the synthesis of cyclic polylactide (cPLA; TOF = 17820 h −1 ) and cyclic polycaprolactone (cPCL; 712800 h −1 ).